O029 Sexual function problems in British 16–21 year olds: Cause for concern?. (30th June 2016) - Mitchell, Kirstin; Geary, Rebecca; Graham, Cynthia; Clifton, Soazig; Mercer, Catherine; Lewis, Ruth; Macdowall, Wendy; Datta, Jessica; Johnson, Anne; Wellings, Kaye
Abstract : Background/introduction: Sexual function is largely absent from the policy discourse on young people's sexual health. The omission is troubling, given the link between low sexual function and indicators of risk (including higher partner numbers, paying for sex, non-consensual sex and STI diagnosis). An absence of data permits this silence. Aim(s)/objectives: To address the gap in empirical data on sexual function problems in young people aged 16 to 21 in Britain. Methods: Descriptive statistics from a national probability survey of 15, 162 British men and women (Natsal-3), undertaken from 2010–2012 using computer-assisted self-interviews (CASI). Complex survey analyses of data from participants aged 16–21 (854 men and 1021 women sexually active in the last year; 262 men and 255 women sexually experienced but not active in the last year). Results: Distressing sexual function problems (>3months in last year) were reported by 9.1% of men and 13.4% of women. Most common among men was reaching a climax too quickly (4.5%) and among women, difficulty reaching climax at all (6.3%). The majority of young people experiencing problems did not seek help, and those that did rarely sought out professionals. Around 6% of those currently sexually active, and 10% of those not so, reported avoiding sex because of sexual function problems. Discussion/conclusion: Sexual function problems are common among young people and are largely unaddressed. Addressing these clear needs will have benefits for other aspects of sexual health. Reassurance in clinical settings and information/advice in educational settings are inexpensive and potentially effective strategies.